2020
DOI: 10.1101/2020.10.14.20212498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of influenza vaccination on trained immunity: impact on COVID-19

Abstract: Every year, influenza causes 290.000 to 650.000 deaths worldwide and vaccination is encouraged to prevent infection in high-risk individuals. Interestingly, cross-protective effects of vaccination against heterologous infections have been reported, and long-term boosting of innate immunity (also termed trained immunity) has been proposed as the underlying mechanism. Several epidemiological studies also suggested cross-protection between influenza vaccination and COVID-19 during the current pandemic. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 35 publications
1
48
2
5
Order By: Relevance
“…9 11-14 This trained immunity may confer non-specific protection against different pathogens, inducing upregulation of pattern recognition receptors and the secretion of proinflammatory cytokines through epigenetic and metabolic reprogramming. [11][12][13][14] Another proposed mechanism is a process called 'emergency Open access granulopoiesis'. 37 This is based on the recent observation that following BCG vaccination in newborns; for example, there is induction of the growth factor granulocyte colony-stimulating factor which, in turn, leads to the rapid production of neutrophils, resulting in additional protection from subsequent infection.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…9 11-14 This trained immunity may confer non-specific protection against different pathogens, inducing upregulation of pattern recognition receptors and the secretion of proinflammatory cytokines through epigenetic and metabolic reprogramming. [11][12][13][14] Another proposed mechanism is a process called 'emergency Open access granulopoiesis'. 37 This is based on the recent observation that following BCG vaccination in newborns; for example, there is induction of the growth factor granulocyte colony-stimulating factor which, in turn, leads to the rapid production of neutrophils, resulting in additional protection from subsequent infection.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Furthermore, in vitro experiment, from multi European research collaboration, confirmed that quadrivalent inactivated influenza vaccine induces trained immunity responses against SARS-CoV-2 that enhance the COVID-19 protection[22]. Many previous studies demonstrated this vaccination benefice for pregnant women, and their newborns protected against influenza via passively acquired antibodies[23].…”
Section: Resultsmentioning
confidence: 99%
“…If negative, another immediate RT-qPCR will be done from nasopharynx specimen If the viral load percentage is estimated clinically (low) between 32% and 05% just one RT-qPCR from the Nasopharynx should be done. 1 st Cq between [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] then control test Cq stays between [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (one week after) 1 st Cq between [16][17][18][19][20][21][22][23][24][25][26][27][28]…”
Section: Clinical Interpretation Of the Expected Percentage Of The VImentioning
confidence: 99%
“…Biologically, it is possible that a long-lasting non-specific of 2019-20 influenza vaccination could have had a general effect on (some) virus infections. 20 Also, an interaction with previous human coronavirus infection and 2019-20 influenza vaccination may result in an indirect effect on SARS-CoV-2 infection. 21 Replication studies and further studies on the effects of a recent influenza vaccination on COVID-19 risk will help better understand whether there is no effect or a small protective effect of influenza vaccination on COVID-19.…”
Section: Discussionmentioning
confidence: 99%